Evolutionary Prisoners＇ Dilemma Game on Scale-Free Networks with Degree-Degree Correlation - 程洪艳 代琼琳 李海红 杨俊忠 (Chinese physics letters, 2010)
Degree-degree correlation and heterogeneity in degree are important topological properties characterizing scale-free networks. We consider an evolutionary prisoners＇ dilemma game on scale-free networks and investigate how degree-degree correlation influences cooperation. It is found that the cooperator frequency displays resonance-like behavior with the variation of Pearson correlation coefficient. A measure on local heterogeneity in a network is proposed and it is realized that cooperation is proportional to the local heterogeneity.